Maximum likelihood cluster reconstruction - Bartelmann, Matthias (The astrophysical journal. Part 2, Letters, 1996)
We present a novel method to reconstruct the mass distribution of galaxy clusters from their gravitational lens effect on background galaxies. The method is based on a least-χ 2 fit of the two-dimensional gravitational cluster potential. The method combines information from shear and magnification by the cluster lens and is designed to easily incorporate possible additional information. We describe the technique and demonstrate its feasibility with simulated data. Both the cluster morphology and the total cluster mass are well reproduced.
Gesehen am 29.09.2017